The complete developer master the full stack with TypeSript, React, Next.js, MongoDB, and Docker - Krause, Martin (No Starch Press, 2024)
"Covers the creation of full-stack web development applications. Topics include building a Node.js server, developing a frontend interface, expanding applications by writing REST and GraphQL APIs, implementing middleware, connecting applications to a MongoDB database, adding OAuth authorization, writing automated tests, and deploying projects as microservices using Docker"--
Includes index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Application software -- Development; Computer programming; Logiciels d'application; Développement; Programmation (Informatique); computer programming